Application of concentration and 2-dimensional stable isotope measurements of methane to constrain sources and sinks in a seasonally stratified freshwater lake - Einzmann, Teresa; Schroll, Moritz; Kleint, Jan F.; Greule, Markus; Keppler, Frank (Frontiers in Environmental Science, 2022)
Methane (CH4) emissions from aquatic systems have recently been comprised to account for up to 50% of global CH4 emissions, with lakes representing one of the largest CH4 sources within this pool. However, there is large uncertainty associated with CH4 emissions from freshwater environments to the atmosphere, because of a lack of understanding in the spatial and temporal dynamics of CH4 sources and sinks, as well as underlying mechanisms and processes. In this study, we investigated the concentrations and stable carbon (δ13C-CH4) and hydrogen (δ2H-CH4) isotope composition of CH4 in a small eutrophic lake (Lake Willersinnweiher) with seasonal stratification and its spatial and temporal variation. We found that while supersaturation of CH4 in the entire water column was present throughout the whole year, the isotopic composition of CH4 in sediment and water column varied depending on lake stratification, physiochemical conditions, and lake depth. During the stratification period, isotopic characteristics of pelagic surface water CH4 differed from littoral and sedimentary CH4, suggesting likely mixing of CH4 from different sources including vertical and lateral input as well as groundwater input and potentially oxic methane production in the mixed surface water layer. Aerobic CH4 oxidation indicated by a strong increase in both δ13C-CH4 and δ2H-CH4 values at the bottom of the oxycline was found to significantly reduce upward migrating CH4 released at the sediment-water interface. In the sediment, stable isotope characteristics of CH4 showed an increasing dominance of the acetoclastic CH4 formation pathway from the pelagic towards the littoral area. Furthermore, the occurrence of sulfate-dependent anaerobic methane oxidation in the sediment was suggested by an increase in δ13C-CH4 and δ2H-CH4 values. During the mixing period, the isotopic CH4 composition of the water column was distinctively less negative than during the stratification period potentially resulting from a greater impact of groundwater CH4 input compared to the stratification period. Our findings implicate that the application of concentrations and dual isotope measurements of CH4 is a promising approach for constraining CH4 sinks and sources in Lake Willersinnweiher and potentially other small lakes to clearly disentangle the complex CH4 dynamics in lakes both spatially and seasonally.